Effects of AI Chatbots on the Effectiveness of Digital Marketing Campaigns and Customer Satisfaction in Indonesia - Najwa Rosyid Attamimi; Fitroh Fitroh (Majalah Bisnis & IPTEK, 2025)
This study explores the influence of AI chatbots on the effectiveness of marketing strategies and customer satisfaction within the Indonesian market. As AI continues to gain traction in marketing practices, businesses are increasingly adopting chatbots to enhance customer interactions and broaden their campaign reach. The research focuses on assessing the impact of AI chatbot integration on campaign efficiency and customer satisfaction. A Systematic Literature Review (SLR) is conducted, encompassing an analysis of industry publications and practical case studies. The findings indicate that AI chatbots significantly enhance interaction levels by providing personalized responses that cater to individual customer needs. However, challenges remain, particularly in building customer trust and addressing gaps in overall satisfaction. These results highlight the potential of AI chatbots to enhance marketing strategies in Indonesia. For businesses to fully realize the benefits of this technology, further innovation and adaptation will be essential.